The Taxonomic Revolution of New World dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) - Cupello, Mario; Silva, Fernando A. B.; Vaz-de-Mello, Fernando Z. (Frontiers in Ecology and Evolution, 2023)
After almost two decades of stagnation, the taxonomy of the New World Scarabaeinae dung beetles has since 1988 been going through a period of great effervescence. Eighty-one complete revisions and 49 supplements have been produced by 85 authors based in 15 countries in the last 35 years, addressing the taxonomic status of 943 species. This is what we christen as the Taxonomic Revolution of New World dung beetles. We review the history and products of this revolution, explore its causes and its apparent exceptionalism among most other New World Coleoptera groups, and point to the many great challenges that still face the scarabaeine taxonomists. An aspect of interest to ecologists is the coevolution of the Taxonomic Revolution with what we call the Ecological Revolution of dung beetles, i.e., the similar expansion in ecological studies about these organisms. We argue that it has been the continuous feedback between these two simultaneous processes that has enabled each of them to exist and flourish: without the Ecological Revolution, the Taxonomic Revolution could not have existed, and vice-versa. Ecologists and taxonomists are partners in the scientific enterprise, symbionts one may say.